Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145331
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative help in chronic disease management

Abstract: Coping with chronic illness disease is a long and lonely journey, because the burden of managing the illness on a daily basis is placed upon the patients themselves. In this paper, we present our findings for how diabetes patient support groups help one another find individualized strategies for managing diabetes. Through field observations of face-to-face diabetes support groups, content analysis of an online diabetes community, and interviews, we found several help interactions that are critical in helping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…We find that parents engage in what Huh and Ackerman [20] referred to as "illness trajectory alignment" as they looked for parents whose children suffered from similar conditions and who maintained similar illness "medical models" [28]. Parents collectively engage in collaborative sensemaking [35] of their children's medical conditions.…”
Section: Facebook Groups For Advocacymentioning
confidence: 99%
“…We find that parents engage in what Huh and Ackerman [20] referred to as "illness trajectory alignment" as they looked for parents whose children suffered from similar conditions and who maintained similar illness "medical models" [28]. Parents collectively engage in collaborative sensemaking [35] of their children's medical conditions.…”
Section: Facebook Groups For Advocacymentioning
confidence: 99%
“…A recent study by Huh and Ackerman of another diabetes forum, dLife.com, specifically examined individuals' interactions around seeking and receiving help [18]. These researchers suggested that individuals operationalize their experiences using their personal illness trajectories.…”
Section: Information Sharing Within Online Health Forumsmentioning
confidence: 99%
“…For example, Maloney-Krichmar & Preece provide an in-depth analysis of a community for people with knee injuries [22]. Huh and Ackerman focus on a lifelong condition -diabetes -and how it is discussed in a particular online diabetes support community [14]. Newman et al move closer towards our goals in their study of people's perceptions of Facebook as a place for sharing health information, especially as they highlight how and why people choose to use social networking sites for health concerns [24].…”
Section: Online Health Communitiesmentioning
confidence: 99%